PENGARUH KEBISINGAN DAN IKLIM KERJA TERHADAP STRES KERJA DI PABRIK PRODUKSI MAKANAN HEWAN - Wiediartini, Wiediartini; Dermawan, Denny (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Noise and heat has become a problem for worker in animal food processing company. The aim of this study was to investigate the influence of noise and heat to stres. Noise and heat data were collected as primary data and stres was collected by questionnaire and analyzed by multiple regression. The result showed relationship between noise, heat and stres (sig 0,003<0.05). A moderate correlation between noise, heat and stres was also observed (r=0,561). No differences between two groups of age, gender and status were found with t test. Reducing noise and heat by engineering and administrative control were necessary execute. There is no need for different treatment to reduce stres between group of gender, age and status.